Patents of Systems and Methods Using Non-Ionizing Radiation for Measuring Rearfoot Deformations: A Review - Gabriel Trujillo-Hernández; Wendy Flores-Fuentes; Luis Roberto Ramírez-Hernández; Oleg Sergiyenko; Moises J. Castro-Toscano; Abelardo Mercado-Herrera; Fabian N. Murrieta-Rico (Inventions)
Individuals’ lifestyles are affected by valgus and varus deformities in the rearfoot, causing pain in the joints and plantar surface due to the misalignment between the tibial and calcaneus. In orthopedics, medical professionals measure this misalignment by using X-ray systems and goniometers. The X-ray emits ionizing radiation that can cause damage through cumulative exposure over a lifetime, whereas the goniometer will produce measurement errors. This patent review conducted a technological search of systems and methods across various databases using inclusion and exclusion criteria. These thirty-five obtained patents provide valuable information about mechanical, electronic, and mechatronic technologies and non-ionizing radiation to evaluate valgus and varus deformities. The patents are classified into stationary mechanisms, stationary electronic devices, dynamic mechanisms, dynamic electronic devices, stationary mechatronic devices, and dynamic mechatronic devices. They are further categorized based on their measurement methods as either visual or automatic. Additionally, the patents are grouped by usage mode into sitting, standing, and walking. This patent review aims to provide medical professionals with little-known techniques for measuring and evaluating the rearfoot alignment.